Peran Teknologi dalam Meningkatkan Partisipasi Masyarakat di Kawasan Wisata Hutan Sagu, Distrik Sentani, Kabupaten Jayapura - Raihana R. J. Ombaier; Lazarus Ramandei; Tommi Tommi (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study aims to examine how technology, particularly social media, plays a role in increasing community participation in the development of the sago forest tourism area in Kampung Sereh, Sentani District, Jayapura Regency. The area holds strong natural and cultural potential, yet its development as a tourist destination remains underutilized. The research adopts a qualitative descriptive approach using interviews, field observations, and document analysis. findings reveal that digital technology-especially social media platform such as Instagram and Facebook-has broadened the reach of tourism promotion. Young people in the community have started to use these platforms to share tourism- related activities and local cultural practices. However, challenges persist, including low digital literacy, limited access to proper devices, and the lack of technical training and assistance. Community participation is evident in various aspects, such as organizing cultural performances, preparing traditional food, and engaging in environmental conservation. This study recommends ongoing digital training and the formation of a community- managed promotional team to support sustainable and inclusive tourism development.